2021
DOI: 10.4314/jafs.v19i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of banditry on income and livelihoods of yam marketers in Shiroro Local Government Area of Niger State, Nigeria

Abstract: The study was on effects of banditry on income and livelihoods of yam marketers in Shiroro Local Government Area of Niger State, Nigeria. Banditry is one the major confronting production and marketing of yam in Shiroro Local Government of Niger State. The activities on banditry over the years have paralysed economic activities since majority of the populace derived their livelihood from farming. The menace posed by banditry has affected rural populace income livelihood thereby making them sojourning in the nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Rural households rely on available physical assets, financial assets, personal freedom, security and satisfaction in order to enhance their livelihood endeavours (Arua, 2013;Miranthi et al, 2014). This finding is in line with that of Mohammed et al (2019) who reported that majority of farmers in Niger and Kogi States had improved livelihood status due to their high involvement in saving schemes. Source: Field survey, 2020…”
Section: Rural Women Livelihood Status Before and During Participatio...supporting
confidence: 55%
See 1 more Smart Citation
“…Rural households rely on available physical assets, financial assets, personal freedom, security and satisfaction in order to enhance their livelihood endeavours (Arua, 2013;Miranthi et al, 2014). This finding is in line with that of Mohammed et al (2019) who reported that majority of farmers in Niger and Kogi States had improved livelihood status due to their high involvement in saving schemes. Source: Field survey, 2020…”
Section: Rural Women Livelihood Status Before and During Participatio...supporting
confidence: 55%
“…Descriptive statistics such as frequency counts and percentages were used to achieve objectives I; objective II was achieved using livelihood status index (Mohammed et al, 2019). This was measured by presenting the list of 38 likely accrued benefits from saving mobilization scheme including physical assets such as block made houses, land (hectares), mattress, tables, chairs, power tiller, radio, sewing machine, cattle, goats, sheep, ox plough, watch, television, telephone, weighing scale, water pumping machine.…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…Other related studies such as Omirin and Okpara (2018), which examined off-the-farm income activities among women in Ido LGA of Oyo State, Nigeria, concentrated on factors that decisively affect the involvement of women in non-farm enterprise, such as lack of credit access, market distance, transportation cost, health risk, poor government support and lack of social safety net. Also, Mohammed et al (2021) assessed the drivers of off-the-farm diversification in Mokwa LGA of Niger State, Nigeria, using a sample of 187 rural women. Their study adopted logit regression and found that marital status and level of education influence rural women’s off-the-farm participation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Diversifying off-the-farm income by Nigerian households has not received much awareness at the national level, because previous studies focused more on rural Nigeria. For example, Mohammed et al (2021) dealt with rural women in Niger state; Omirin and Okpara (2018) focused on rural women of Ido LGA in Oyo state; Ogbanje et al (2015) studied rural households in Benue, Kogi and Niger states; and Babatunde and Qaim (2009) studied rural households in Kwara State. However, none of the previous studies that employed national-level data such as Adeyo et al (2019), Corral and Radchenko (2017), Shehu and Abubakar (2015) used four waves of the Nigeria General Household Survey (NGHS) panel data, namely 2010/2011, 2012/2013, 2015/2016 and 2018/2019 datasets, to investigate the drivers of off-the-farm income diversification patterns in the rural and urban sectors across the six geopolitical zones in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Information gathered from respondents, via a well-structured questionnaire and focus group discussion revealed that, that banditry has negatively affected food production in the Northwest (Olarewaju and Kyarem, 2021). In Niger state, North-central Nigeria, banditry has shown to paralyzed farming and economic activities in the region (Mohammed et al, 2021). This suggests the need to provide adequate security to rural farmers to strengthen food production in the affected regions (Abdussalam et al, 2022).…”
Section: Armed Banditrymentioning
confidence: 99%